Design of a two D.O.F robot arm with a gripper - 415103 Anoop Sehgal Paras Ram (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Electrical Engineering (Mechatronics)) - Universiti Teknologi Malaysia, 2003